Properties of Ethoxylated Castor Oil Acid Methyl Esters Prepared by Ethoxylation over an Alkaline Catalyst. Issue 2 (25th December 2014) - Zhang, Qian; Sun, Yongqiang; Zhi, Lifei; Zhang, Yong; di Serio, Martino
Abstract: The synthesis and properties of ethoxylated castor oil acid methyl esters (ECAME) were investigated. Ethylene oxide (EO) can react directly with the ester group and hydroxyl group of castor oil acid methyl esters in the presence of an alkaline catalyst. ECAME with different average EO adduct numbers were synthesized and, through testing the degree of EO addition, it was found that only a few EO moieties (2–4) inserted into the hydroxyl group. In addition, the physicochemical properties of ECAME were studied. ECAME can be used as nonionic surfactants with good properties.